STRATEGI PENGEMBANGAN DINAS PEMBINAN POTENSI MARITIM (DISPOTMAR) KODAERAL XI DALAM RANGKA MENINGKATKAN EFEKTIVITAS PEMBINAAN POTENSI MARITIM - Rusydi, Thoriqul; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
The Maritime Potential Development Agency (Dispotmar) of Kodaeral XI is one of the executive elements of Kodaeral XI that has the duty to organize the development of functions and carry out activities to enhance maritime potential, including the development of human resources, natural and artificial resources, national facilities and infrastructure in the maritime sector, as well as the dynamism of marine development. Dispotmar Kodaeral XI also carries out territorial functions, especially within the operational area of Kodaeral XI. In order to support effectiveness in developing maritime potential, there are several problems that occur and stand out in the field of regional resilience development (Bintahwil), social communication (komsos), community service, maritime service industry (Injasmar), fisheries law, and infrastructure. The development strategy of the maritime potential development agency (Dispotmar) of Kodaeral XI in supporting the effectiveness of maritime potential development is expected to address some of the existing problems. The stage carried out is the identification and evaluation of internal and external factors, selection of strategies using the SWOT quadrant matrix followed by the SWOT matrix for selected alternative strategies and Borda to determine the selected priority strategy. From the research results, a Stability Strategy was obtained, which is to maximize the improvement of weakness factors to capitalize on opportunities, and from the weight calculation, it is known that the WO 3 strategy has the highest weight and is the priority strategy, namely Increasing the number of personnel in Maritime Potential Development Non-Commissioned Officers (Babinpotmar) by utilizing government policies in realizing the world's maritime axis and government policies in managing marine resources